Evaluation of PPP road projects in Greece. Issue 2 (10th June 2019) - Marinelli, Marina
Abstract : Purpose: The purpose of this paper is to explore and evaluate the problems encountered by five major road projects recently implemented in Greece as public–private partnerships (PPP) and make recommendations for improvement of the relevant managerial practices and contractual clauses for the benefit of similar future projects. Design/methodology/approach: A qualitative approach was adopted in this research as only senior engineers with specific managerial experience were deemed suitable for the purposes of this research. In total, 15 semi-structured interviews were conducted with CEOs of the PPPs and heads of independent engineers involved in the projects' implementation as well as with senior officials of two Greek Ministries. Findings: The experts identified different areas of weakness relevant to the revenue risks, the planning of the scope, the management of designs and legal permits as well as the toll policy selected. They also made specific recommendations for the streamlining of the relevant procedures in the future. Practical implications: The experts' opinions and recommendations constitute a solid basis for the achievement of higher efficiency in the management of future PPP projects worldwide. Originality/value: This research offers a holistic perspective to PPP project management as it sheds light to the problems encountered by the Greek PPP programme as a whole and incorporates the experience gained at the contracts' renegotiation. The research draws from the experience of experts and offers recommendations for systemic improvements which can be widely applied in any geographical context.